UTILIZING TRANSLANGUAGING IN TEACHING ESP TO CULINARY ART STUDENTS IN INDONESIA: CHALLENGES AND EFFORTS - Gufron; Nufus, Tatu Zakiyatun (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2023)
Translanguaging is a pedagogical strategy that can be used to assist students in understanding the material in the classroom and this strategy plays an important role for teachers in conducting classes of English for specific purposes (ESP) in culinary art classrooms. The study was conducted to examine translanguaging utilization in teaching ESP for culinary art students and find out the challenges and effort that teachers have in the classroom. The research used a case study in a culinary art classroom of Almansyuriyah Vocational School at Tangerang and descriptive analysis was used to analyse data that has been collected through classroom observation and interview with a teacher and 20 students. The result explained that utilizing translanguaging in the classroom raises students’ understanding of the material given because students can use the home language (L1) to understand the context and elaborate on the target language. Finally, Translanguaging as a pedagogical strategy can be utilized to assist students in understanding English for specific purposes in culinary art classrooms in Indonesia.